The impact of financial globalization and financialization on the economy in the current crisis through banking corporate governance - Juan Antonio Azkunaga; Leire San-Jose; Sara Urionabarrenetxea (Contemporary Economics, 2013)
This work analyzes the role of governance of financial entities in the current crisis. Neoliberal economic policies, deregulation and liberalization have characterized financial globalization, giving rise to the financialization of the economy. This paper, using the analysis-synthesis method, shows that the corporate governance of entities has adapted to the new social environment under the influence of the interests of the investors. The results of this paper suggest the need to monitor the over-emphasis on the maximization of short-term shareholder value without relativizing the risk taken to achieve it, as such, the emphasis on short-term shareholder value is considered a crucial contributing factor to the present crisis.
Keywords: F30; G01; G21; G34; 330; corporate governance; banks; globalization; financial crisis; institutional investors